Blood flow restriction exercise stimulates mTORC1 signaling and muscle protein synthesis in older men - Fry, Christopher S. (American Physiological Society, 2010)
The loss of skeletal muscle mass during aging, sarcopenia, increases the risk for falls and dependence. Resistance exercise (RE) is an effective rehabilitation technique that can improve muscle mass and strength; however, older individuals are resistant to the stimulation of muscle protein synthesis (MPS) with traditional high-intensity RE. Recently, a novel rehabilitation exercise method, low-intensity RE, combined with blood flow restriction (BFR), has been shown to stimulate mammalian target of rapamycin complex 1 (mTORC1) signaling and MPS in young men. We hypothesized that low-intensity RE with BFR would be able to activate mTORC1 signaling and stimulate MPS in older men. We measured MPS and mTORC1-associated signaling proteins in seven older men (age 70 ± 2 yr) before and after exercise. Subjects were studied identically on two occasions: during BFR exercise [bilateral leg extension exercise at 20% of 1-repetition maximum (1-RM) with pressure cuff placed proximally on both thighs and inflated at 200 mmHg] and during exercise without the pressure cuff (Ctrl). MPS and phosphorylation of signaling proteins were determined on successive muscle biopsies by stable isotopic techniques and immunoblotting, respectively. MPS increased 56% from baseline after BFR exercise (P < 0.05), while no change was observed in the Ctrl group (P > 0.05). Downstream of mTORC1, ribosomal S6 kinase 1 (S6K1) phosphorylation and ribosomal protein S6 (rpS6) phosphorylation increased only in the BFR group after exercise (P < 0.05). We conclude that low-intensity RE in combination with BFR enhances mTORC1 signaling and MPS in older men. BFR exercise is a novel intervention that may enhance muscle rehabilitation to counteract sarcopenia.